VITAMIN D DURING PREGNANCY: A STRONG PLAYER IN A BATTLE FOR TWO - Adina Ghemigian; Andra Cocolos; Nicoleta Dumitru; Eugenia Petrova; Ana Valea; Mara Carsote (Romanian Medical Journal, 2018)
Vitamin D represents a complex endocrine system with multifunctional levels of action, including during pregnancy. This is a short review of literature based on PubMed research. Vitamin D is linked to numerous divergent normal and abnormal functions of the human body. This becomes crucial during pregnancy. Specific metabolism during this period of time includes the role of placenta as provider of additional calcitriol resources. The excess of calcitriol is sustained by adequate levels of maternal 25-hydroxyvitamin D. Different conditions as gestational diabetes have been linked to maternal hypovitaminosis D. Vitamin D also prepares neonates immune system. Vitamin D represents a strong player during pregnancy from mothers and child’s as well point of view.